Optimizing Public Communication in the Digital Era: A Case Study of the Ministry of Communication and Information Technology in Indonesia - Susanti, Tristiani; Anom, Erman; Iswadi, Iswadi (Universitas Ahmad Dahlan, 2023)
Effective public communication is pivotal in today's digital age, where the interplay of various channels and media platforms shapes societal interactions. This study delves into the intricate domain of public communication, focusing on the Ministry of Communication and Information Technology (KOMINFO) in Indonesia. Employing qualitative research methods, including case studies, observations, interviews, and document analysis, this research investigates KOMINFO's strategies, particularly its social media communication initiatives. The study illuminates the challenges faced by the government in bridging communication gaps with the public and explores the innovative solutions deployed, including the utilization of social media platforms, digital literacy programs, and the engagement of skilled communicators. Despite commendable efforts, challenges persist, especially in the context of crisis communication, such as during the COVID-19 pandemic. The study concludes by emphasizing the need for ongoing research to align expectations with outcomes and offers valuable insights for policymakers and practitioners aiming to optimize public communication strategies in the evolving digital landscape.